PROBABILITY OF SLOPE DESIGN FAILURE ANALYSIS PRIMARY TIN DEPOSIT ON OPEN PIT MINE DESIGN PT XYZ - Irfan Kosasih, Raihan
PT. XYZ is a tin mining company in North Bangka Regency, Bangka Belitung Province have been planned to mine and have two alternative mine open pit, that is pit 8 and pit 10. For safety and smooth mining operation processes in the future, then needed to analyze the stability of the slope. Analysis of the slope stability used is a probability of failure analysis, based on Ministerial of Energy and Mineral Resources decree Number 1827 K / 30 / MEM / 2018, so that it can give conclusions whether or not the slope is safe. Analysis the probability of failure is started by collecting laboratory test data that form of unit weight, cohesion and internal friction angle that have been sorted from the smallest to the largest value. Then a goodness of fit test is performed to select the best distribution function, using the Kolmogorov-Smirnov method followed by the Akaike Information Criterion. The output are mean, standard deviations, relative maximum, and relative minimum that will be the input parameters for the Monte-Carlo simulation method using Slide 6.0.25 software. The results of analysis the probability of failure using Slide 6.0.25 software with pore water pressure (hu) of 0.6 that for an alternative design of pit 8 cross section A-A' has 0% PK with right FK 2.99 and left FK 2.97, for cross section B-B' right PK 0% with FK of 1.19 and left PK 0% with FK of 3.05, for cross section C-C' has PK 0% with right FK 2.95 and left FK 1.48. While for the alternative design of pit 10 A-A 'cross section has PK 0% with right FK 2.94 and left FK 3.28, for cross section B-B' has PK 0% with right FK 1.43 and left FK 2.99, for cross section C-C' has PK 0% with right FK 2.80 and left FK 1.51. Based on Ministerial of Energy and Mineral Resources decree Number 1827 K / 30 / MEM / 2018 No. 1827 K / 30 / MEM / 2018 declared global slope safe for all consequences of failure if FK dinamic ? 1.1 and FK Static 1.3-1.5 with a failure probability value ? 5% and also interramp safe for all consequences of failure if FK dinamic ? 1.1 and FK Static 1.2-1.3 with a failure probability value ? 10% so that all slopes in the alternative design pit 8 and pit 10 are safe for all consequences of failure.